Improvement of Cardiac Stem Cell Sheet Therapy for Chronic Ischemic Injury by Adding Endothelial Progenitor Cell Transplantation: Analysis of Layer-Specific Regional Cardiac Function. Issue 10 (October 2014) - Kamata, Sokichi; Miyagawa, Shigeru; Fukushima, Satsuki; Nakatani, Satoshi; Kawamoto, Atsuhiko; Saito, Atsuhiro; Harada, Akima; Shimizu, Tatsuya; Daimon, Takashi; Okano, Teruo; Asahara, Takayuki; Sawa, Yoshiki
The transplantation of cardiac stem cell sheets (CSC sheets) is a promising therapeutic strategy for ischemic cardiomyopathy, although potential ischemia in the transplanted area remains a problem. Injected endothelial progenitor cells (EPCs) can reportedly induce angiogenesis in the injected area. We hypothesized that concomitant CSC sheet transplantation and EPC injection might show better therapeutic effects for chronic ischemic injury model than the transplantation of CSC sheets alone. Scaffold-free CSC sheets were generated from human c-kit-positive heart-derived cells. A porcine chronic ischemic injury model was generated by placing an ameroid constrictor around the left coronary artery for 4 weeks. The animals then underwent a sham operation, epicardial transplantation of CSC sheet over the ischemic area, intramyocardial injection of EPCs into the ischemic and peri-ischemic area, or CSC sheet transplantation plus EPC injection. The efficacy of each treatment was then assessed for 2 months. Speckle-tracking echocardiography was used to dissect the layer-specific regional systolic function by measuring the radial strain (RS). The epicardial RS in the ischemic area was similarly greater after treatment with the CSC-derived cell sheets alone (19 ± 5%) or in combination with EPC injection (20 ± 5%) compared with the EPC only (9 ± 4%) or sham (7 ± 1%) treatment. The endocardial RS in the ischemic area was greatest after the combined treatment (14 ± 1%), followed by EPC only (12 ± 1%), compared to the CSC only (11 ± 1%) and sham (9 ± 1%) treatments. Consistently, either epicardial CSC sheet implantation or intramyocardial EPC injection yielded increased capillary number and reduced cardiac fibrosis in the ischemic epicardium or endocardium, respectively. Concomitant EPC injection induced the migration of transplanted CSCs into the host myocardium, leading to further neovascularization and reduced fibrosis in the ischemic endocardium, compared to the CSC sole therapy. Transplantation of CSC sheets induced significant functional recovery of the ischemic epicardium, and concomitant EPC transplantation elicited transmural improvement in chronic ischemic injury.